The modern features of optimal therapy of salpingoforite - О. В. Булавенко; Д. Г. Коньков; О. М. Гончаренко (Publishing House TRILIST, 2017)
The aim of the prospective study was to investigate the clinical efficacy of Tamistol and Bifiten in the complex treatment of salpingoophoritis. Patients and methods. The study involved 152 patients of reproductive age with salpingoophoritis. All women were divided into 3 groups: I - 48 patients received traditional therapy; II - 54 patients who received complex anti-inflammatory treatment with vaginal application of a combined drug containing neomycin sulfate 35,000 IU, polymyxin B sulfate 35,000 IU and nystatin 100,000 IU; III - 50 women, each of whom in addition to traditional therapy received Tamistol and the synbiotic Bifiten. The comparative assessment of the effectiveness of treatment was conducted on the basis of regression of women's complaints and the results of bacteriological research in dynamics. Results. The local application of suppositories Tamistol or combined drug with neomycin sulfate, polymyxin B sulfate and nystatin had a pronounced clinical effect in the treatment of salpingooophoritis. However, the use of suppositories of Tamistol and Bifiten capsules were more effective than the use of combined drug to reduce the incidence of dysbiosis (RR 2.01, 95% CI 1.14-3.53, p = 0.02 and RR 4.63, 95% CI 1.43-15.04, p = 0.01), for a higher number of lactobacilli (RR 1.99, 95% CI 1.17-3.40, p = 0.011 and RR 5.45 95% CI 1,71-17,41, p = 0,004) on the 14th and 30th day of the study. Conclusion. Use of suppositories Tamistol and capsules Bifiten was clinically highly effective in the complex therapy of salpingoophoritis. The combination of suppositories Tamistol and Bifiten capsules per os requires further investigation.